(untitled) (Revista Electrónica REDINE, 2018)
Creativity and innovation are used with increasing frequency in the educational field and form a major part in the strategies that should be encouraged, since the early years of life, by teachers and educational institutions concepts. The human being finds on his way constant challenges make it essential to be educated in creativity. The changes that have occurred in education reflect the need to keep up with the constant innovations and the various strategies that have been devised to improve the man of the future and therefore to society. This paper aims to review some relevant aspects related to creativity, innovation and educational change.